2017
DOI: 10.4103/atm.atm_15_17
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intermittent fasting on the circadian pattern of melatonin while controlling for caloric intake, energy expenditure, light exposure, and sleep schedules: A preliminary report

Abstract: AIMS:We hypothesized that if we control for food composition, caloric intake, light exposure, sleep schedule, and exercise, intermittent fasting would not influence the circadian pattern of melatonin. Therefore, we designed this study to assess the effect of intermittent fasting on the circadian pattern of melatonin.METHODS:Eight healthy volunteers with a mean age of 26.6 ± 4.9 years and body mass index of 23.7 ± 3.5 kg/m2 reported to the Sleep Disorders Center (the laboratory) on four occasions: (1) adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Studies that assessed changes in core body temperature during Ramadan diurnal IF have reported conflicting results (Table 1). In general, studies that assessed the circadian rhythm during Ramadan diurnal intermittent fasting can be divided into two categories: category 1 encompasses studies that examined the changes in some markers of the circadian clock in an unconstrained “free-living environment” without controlling for confounders and lifestyle changes such as meal composition, caloric intake, total sleep time, energy expenditure, or light exposure,2427 and category 2 encompasses studies that controlled for the above confounders 2830…”
Section: Impact Of Diurnal If On the Circadian Rhythmmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that assessed changes in core body temperature during Ramadan diurnal IF have reported conflicting results (Table 1). In general, studies that assessed the circadian rhythm during Ramadan diurnal intermittent fasting can be divided into two categories: category 1 encompasses studies that examined the changes in some markers of the circadian clock in an unconstrained “free-living environment” without controlling for confounders and lifestyle changes such as meal composition, caloric intake, total sleep time, energy expenditure, or light exposure,2427 and category 2 encompasses studies that controlled for the above confounders 2830…”
Section: Impact Of Diurnal If On the Circadian Rhythmmentioning
confidence: 99%
“…None of the above studies accounted for potential confounders that may accompany Ramadan and affect the measured melatonin levels. In a subsequent study, we attempted to overcome those limitations by assessing circadian profiles of serum melatonin during diurnal IF outside Ramadan (to assess the impact of diurnal IF act in the absence of the lifestyle changes associated with Ramadan) and during the second week of Ramadan while controlling for light exposure, sleep pattern, total sleep time, and meal composition 28. In eight healthy volunteers, serum melatonin was measured at five time points (22:00, 02:00, 04:00, 06:00, and 11:00) three times: 4 weeks before Ramadan where volunteers were asked to perform diurnal IF (fasting outside the month of Ramadan) for 1 week, 1 week before Ramadan during which volunteers were not fasting and living a routine life, and during the second week of Ramadan while performing diurnal IF.…”
Section: Impact Of Diurnal If On the Circadian Rhythmmentioning
confidence: 99%
“…For details about study design, we refer the reader to previous studies assessing neurohormonal changes during Ramadan. [ 8 24 ]…”
Section: Methodsmentioning
confidence: 99%
“…We used the same intermittent fasting protocol described in previous studies. [ 8 23 24 ] During the fasting periods (FOR and Ramadan), the participants were asked to fast from dawn to sunset.…”
Section: Methodsmentioning
confidence: 99%
“…Reviewing all studies that aimed to assess the circadian rhythm changes during Ramadan reveals two types of studies: (1) studies that were conducted in a non-constrained environment and did not control for lifestyle changes, caloric intake, and nocturnal meal timings, and these studies reported rapid and significant delays in bedtime and rising time (45)(46)(47); and (2) recent studies that accounted for sleep/wake schedule, sleep duration, light exposure, caloric consumption, meal timings and energy expenditure, which demonstrated no changes in circadian rhythm during fasting (48)(49)(50). In the second group, meals were served early at night, the participants slept early according to their usual routine and then woke up for the predawn meal in the early morning.…”
Section: Effects On Circadian Rhythmmentioning
confidence: 99%